Reading Adapted Texts of Young Adult Fiction and Reading Motivation of Pupils With Speech and Language Disorders - Vizjak Puškar, Nika; Vršnik Perše, Tina; Haramija, Dragica (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
The research studied how reading of adapted young adult fiction effects reading motivation of Slovene elementary school pupils with speech and language disorders. The research involved 50 pupils from the last three years of elementary school. Typically, pupils with these disorders do not enjoy reading during adolescence, as texts that would be suitable to their age and interests in terms of content are most often incomprehensible or linguistically too demanding for them. For the purpose of the research, we adapted two complete works of Slovene literature into an easy-to-read form (passages version in easy language). Pupils intensively read the adapted texts and also looked at the originals. This had positive effects both on their comprehension of the literary texts as well as their reading motivation. The results of the research demonstrated that adapted texts positively influence the reading motivation of pupils and their perception of literature.